THE EFFECT OF LEADERSHIP, MOTIVATION, APPLICATION OF LEARNING ORGANIZATION ON PERFORMANCE OF EMPLOYEES IN THE REGIONAL SECRETARIAT OF CENTRAL LAMPUNG (Administratio, 2018)
ABSTRACT. The demands of good public servicesneed quickly response from government. It caused of the perfomance of civil servants still poor. Public services become the purposes of public organization. So, make a good performance of employees in public organization become so important to keep the society trust. This research was conducted at locations Secretariat of district, Middle Lampung. The object of this research is all employees in the Regional Secretariat of district Middle Lampung. In this case the technique of collecting data from samples / sources of primary data by asking a list of written questions / questionnaire, the data analysis techniques using multiple linear regression equation. The results of this research may indicate the relationship between Leadership, Motivation, Implementation of Learning Organization with employee job performance.